The density, mechanical, and shielding characteristics of a BaO–Al2O3–P2O5 doped with a V2O5 glass system: Theoretical and simulation study. (June 2023) - Moustafa, Essam B.; Abdel-wahab, Mohamed Sh; Hammad, Ahmed H.
Abstract: Using the conventional melt-annealing method, barium aluminum phosphate glass doped with different concentrations of vanadium pentoxide was synthesized. The theoretical evaluation of glass density was compared to the experimental results to calculate the mechanical parameters of Young's modulus, Poisson's ratio, bulk modulus, shear modulus, and longitudinal modulus. The National Institute of Standards and Technology – Extrapolated Center of Mass (NIST-XCOM) database was used to stimulate the behavior of glass in response to radiation at different levels between X-rays and gamma rays ranging from 22.16 keV to 1.4081 MeV. At 22.16 keV, the base sample's mass attenuation coefficient ( μ m ) was 10.62 cm 2 /g, decreasing to 2.858 cm 2 /g at 36.38 keV. At a photon energy of 32.06 keV, the μ m value increases from 3.973 cm 2 /g to 4.006 cm 2 /g as the V2 O5 content increases. At photon energies of 661 keV, the μ m decreases from 0.07698 cm 2 /g to 0.07689 cm 2 /g. The half-value layer ( HVL ), the tenth value layer ( TVL ), and the mean free path ( MFP ) for the base glass increase from 0.237 mm to 5 cm, 0.79 mm to 16.593 cm, and 0.343 mm to 7.205 cm, respectively, with an increase in V2 O5 content from 0.28 mm to 5.943 cm, 0.93 mm to 19.756 cm, and 0.404 mm to 8.576 cm at 2.5% V2 O5 . Highlights: Evaluation of BaO–Al2 O3 –P2 O5 –V2 O5 glasses mechanical and shielding properties. The ionic packing ratio was used to derive the mechanical properties. The NIST-XCOM database stimulated the glass with 22.16 keV to 1.4081 MeV radiation. From 22.16 keV to 121.78 keV, all glass samples had a low MFP.